Blood Transfusion and the Risk of Acute Kidney Injury Among Patients With Acute Coronary Syndrome Undergoing Percutaneous Coronary Intervention. (September 2016) - Karrowni, Wassef; Vora, Amit Navin; Dai, David; Wojdyla, Daniel; Dakik, Habib; Rao, Sunil V.
Abstract : Background—: Acute kidney injury (AKI) complicating percutaneous coronary intervention (PCI) is associated with adverse clinical outcomes. To date, no studies have evaluated the association of blood transfusion with AKI in patients undergoing PCI. Methods and Results—: We used a retrospective cohort study of all patients with acute coronary syndrome undergoing PCI from CathPCI Registry (n=1 756 864). The primary outcome was AKI defined as the rise in serum creatinine post procedure ≥0.5 mg/dL or ≥25% above baseline values. AKI developed in 9.0% of study sample. Patients with AKI were older, more often women, and had high prevalence of comorbidities, including diabetes mellitus, hypertension, and advanced stages of chronic kidney disease at baseline. Blood transfusion was utilized in 2.2% of patients. In the overall sample, AKI developed in 35.1% of patients who received transfusion versus 8.4% of patients without transfusion (adjusted odds ratio, 4.87 [4.71–5.04]). In the subgroup of patients who sustained bleeding event and received transfusion, the rate of AKI was significantly increased across all preprocedure hemoglobin levels versus no blood transfusion. Similar findings were seen in the subgroup of patients with no bleeding event. Conclusions—: Blood transfusion is strongly associated with AKI in patients with acute coronary syndrome undergoing PCI. Further investigation is needed to determine whether a restrictive blood transfusion strategy might improve PCI outcomes by reducing the risk of AKI. Abstract : Supplemental Digital Content is available in the text.